Geo-grafias insurgentes: corpo e espaço nos romances Ponciá Vicêncio e Becos da memória de Conceição Evaristo - Queiroz, Ana Maria Martins (2017)
The current context of geographic science can be understood as a period marked by transformations in the way of understanding the socio-spatial dynamics, which has headed this science to go to a variety of themes as difference, gender, race and sexuality. In this sense, geographers try to cover the multiplicity of sense that can be attributed to space. Before this reconfiguration, the geographic knowledge has been permeated, therefore, by issues that are linked to intersection between body and space. Therefore, I searched in the dialogue between Geography and black literature, elements that could make possible to comprehend the multiple spatialities. This way, this thesis is based on the hypothesis that the literary narratives by Conceição Evaristo, a black writer woman, are marked by the relationship between body and space. I constructed the analysis based on the novels Ponciá Vicêncio (2003) and Becos da Memória (2006) by the referred author, which defines her narratives as escrevivência (“write-living”). For her, her writing is marked, greatly, by her socio-spatial trajectory and by her memories, which permits her to create and write from her experiences as a black woman. The novels analyzed have significant inscriptions of intersectionality, once the characters’ stories are constituted, in a significant part, by the relationship between gender, race and space. This way, they made possible to me to stablish an intersectional analysis whereby I understood that the spatialities of black women are constituted, also, by their bodies. These bodies have the possibilities and the limits these people find in their everyday lives, demarcating which spaces are forbidden and the ones that are possible to be occupied. To develop this research, I made use of Discourse Analysis (DA) as methodology, in a way to identify the discursive memories, formations and ruptures found in the narratives. Beyond that methodological procedure, I searched to find the spatial inscriptions that make relation with the body through the survey of terms and expressions that could indicate the intersection between these aspects. This way, I identified how the intersectionality is constituted in these novels among the mentioned categories.